Lung injuries associated with e-cigarette use: an integrative review - Souza Mota, Caio; Abreu Santos Nunes, Gustavo; Borges de Mattos, Álex; Henryque do Nascimento, Thyago; Gonçalves Magalhães, Itamar (Seven Editora, 2023)
Objective: to investigate data on lung injuries associated with the use of electronic cigarettes. Methodology: constitutes an integrative literature review in which articles published from 2017 to 2022 on the LILACS (Latin American and Caribbean Literature in Health Sciences) and PubMed platforms with the following descriptors “pulmonary lesion” (“Lung injury"), "vaping" and "acute lung injury". Free articles available on the platforms published in the aforementioned period in English and Portuguese were read. In addition, articles that were dissonant with the descriptors were excluded, as well as studies that were not free and those that were published outside the target date. Results: 118 studies were requested based on the descriptors, however, after applying the inclusion and exclusion criteria, only 9 articles were selected to compose the body of the present study and, then, subjected to a thorough analysis for responsible and impartial extraction of information . Conclusion: based on the texts examined, there is a clear relationship between the inhalation of vaporized substances and lung lesions and structural alterations that are capable of leading to a characteristic symptomatological condition, which may progress to the need for mechanical ventilation and death. DOI: https://doi.org/10.56238/devopinterscie-097